SdiA Enhanced the Drug Resistance of Cronobacter sakazakii and Suppressed Its Motility, Adhesion and Biofilm Formation - Cheng, Chuansong; Yan, Xiaotong; Liu, Binxiong; Jiang, Tao; Zhou, Ziwen; Guo, Fengting; Zhang, Qianwen; Li, Changcheng; Fang, Ting (Frontiers in Microbiology, 2022)
Cronobacter sakazakii is a common foodborne pathogen, and the mortality rate of its infection is as high as 40–80%. SdiA acts as a quorum sensing regulator in many foodborne pathogens, but its role in C. sakazakii remains unclear. Here, we further determined the effect of the sdiA gene in C. sakazakii pathogenicity. The SdiA gene in C. sakazakii was knocked out by gene editing technology, and the biological characteristics of the ΔsdiA mutant of C. sakazakii were studied, followed by transcriptome analysis to elucidate its effects. The results suggested that SdiA gene enhanced the drug resistance of C. sakazakii but diminished its motility, adhesion and biofilm formation ability and had no effect on its growth. Transcriptome analysis showed that the ΔsdiA upregulated the expression levels of D-galactose operon genes (including dgoR, dgoK, dgoA, dgoD and dgoT) and flagella-related genes (FliA and FliC) in C. sakazakii and downregulated the expression levels of related genes in the type VI secretion system (VasK gene was downregulated by 1.53-fold) and ABC transport system (downregulated by 1.5-fold), indicating that SdiA gene was related to the physiological metabolism of C. sakazakii. The results were useful for clarifying the pathogenic mechanism of C. sakazakii and provide a theoretical basis for controlling bacterial infection.